Public Private Partnership in Storage of Food Grains Model Concession Agreement - Planning Commission (Planning Commission, 2014)
Over the past three decades, India has been facing a serious challenge in managing its large stocks of food grains which are procured by government agencies, both for meeting the support price obligations of the government and for supply of subsidised food grains under the public distribution system. It is estimated that post-harvest losses of such food grains are as high as 10 percent, largely due to lack of modem storage facilities. This constitutes a huge national waste in terms of food as well as public money. Besides shortage of storage capacity, there is virtually a complete absence of modem storage facilities like silos, which can store food grains for longer periods while preserving their quality.
Planning Commission Government Of India
Planning Commission Government of India